2016
DOI: 10.1007/s00259-016-3591-2
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater variability of visual interpretation and comparison with quantitative evaluation of 11C-PiB PET amyloid images of the Japanese Alzheimer’s Disease Neuroimaging Initiative (J-ADNI) multicenter study

Abstract: Inter-rater agreement was almost perfect in C-PiB PET scans. Positive or negative decision by visual interpretation was dichotomized by a cut-off value of mcSUVR = 1.5. As some cases of disagreement among raters tended to show low mcSUVR, referring to quantitative method may facilitate correct diagnosis when evaluating images of low amyloid deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 31 publications
1
83
1
1
Order By: Relevance
“…This result is consistent with kappa values in the range 0.73–0.82 reported by Harn et al [18], who evaluated the agreement among three experienced raters in the reading of 55 florbetapir PET scans, and with the kappa values reported by Buckley et al [19], who found that most values were greater than 0.80. Yamane et al [20] found a slightly higher kappa value of 0.89 with 11 C-based Pittsburgh compound B, which may be explained by the fact that 57 normal controls were included in the test cohort of 162 patients. Patients without cognitive impairment might exhibit lower variability leading to higher kappa values than patients with various levels of cognitive impairment, as those in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with kappa values in the range 0.73–0.82 reported by Harn et al [18], who evaluated the agreement among three experienced raters in the reading of 55 florbetapir PET scans, and with the kappa values reported by Buckley et al [19], who found that most values were greater than 0.80. Yamane et al [20] found a slightly higher kappa value of 0.89 with 11 C-based Pittsburgh compound B, which may be explained by the fact that 57 normal controls were included in the test cohort of 162 patients. Patients without cognitive impairment might exhibit lower variability leading to higher kappa values than patients with various levels of cognitive impairment, as those in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-labeled PiB (Florbetapir) was synthesized with NEPTIS ® plug-01, intravenously injected for 9 participants at an Okayama University-affiliated hospital, and 60-90 min later PET images were detected for 30 min. For two AD patients at Oita University, 11 C-PiB was injected to take PET images [9,10]. As the whole cerebellar region of interest (ROI) for reference, an average of standard uptake value (SUV) from 6 cerebral cortical areas were calculated in order to analyze positive or negative for PiB-PET (positive for more than 1, negative for 1 or less).…”
Section: Pet Imagingmentioning
confidence: 99%
“…Diagnosis of AD is usually based on clinical criteria, but may be supported by biochemical markers such as a decreased amyloid-␤ (A␤) 42 [3], and increased A␤ oligomer [4,5] and tau protein in cerebrospinal fluid (CSF) [3]. Radiological analyses are also sometimes undertaken as supportive biomarkers of AD with single photon emission computed tomography (SPECT) for evaluating cerebral blood flow [6,7] and positron emission tomography (PET) for A␤ using Pittsburgh compound B (PiB) [8][9][10] and tau [11][12][13]. However, blood samples are more feasible and plausible than CSF or radiological biomarkers for screening emerging number of potential AD and other dementias [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…All PiB-PET images were visually interpreted and classified as positive or negative by two PiB-PET expert physicians after consultation. 13,14 Quantitative analysis of amyloid deposition was performed with the automated method. 15 We used PMOD software (PMOD Technologies, Zurich, Switzerland) for all image analysis.…”
Section: Carbon-11-labelled Pittsburgh Compound B Positron Emission Tmentioning
confidence: 99%